Projecting the potential impact of COVID-19 school closures in Poland and abroad on the students sense of security. Analysis of the phenomenon in the light of research in the literature on the subject = Prognozowanie potencjalnego wpływu zamknięcia szkół w Polsce i za granicą z powodu COVID-19 na poczucie bezpieczeństwa uczniów - Frączkowska, Kinga (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The fate of the whole world changed in 2020, when the COVID-19 pandemic tarnished the organization of the 2019-2020 school year. Education systems around the world have tried to adapt to the restrictions in force. Meeting the needs of pupils, but also their families, was not easy overnight. At the beginning of the pandemic, anxiety and uncertainty regarding the organization of a fast-track alternative to on-site teaching in schools accompanied every person working in the education system. The great responsibility in deciding how schools, universities, kindergartens, nurseries and educational institutions of all kinds were to be run rested with the ministers of science and education and the directors and rectors of these institutions.
Keywords: pandemic; teaching; sense of security; online learning; pandemia; nauczanie; poczucie bezpieczeństwa; kształcenie na odległość